2014
DOI: 10.5539/jas.v6n9p120
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Saccharification Conditions of Acid-pretreated Sweet Sorghum Straw Using Response Surface Methodology

Abstract: This study focused on the cellulase production from C. versicolor TD17, white rot fungi. The maximum cellulase activity of 0.897 U/ml was obtained after 5 days of cultivation using 20 g/l cellobiose as a carbon source and 2 g/l ammonium sulfate supplemented with 0.3 g/l urea as nitrogen sources. Enzymatic saccharification of acid-pretreated sweet sorghum straw (SSS) using in house cellulase was optimized using Response Surface Methodology (RSM), variable five-code-level, four-factor; 1.0-7.0% w/v acid-pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…On the other hand the experimental values for the saccharification process were 3.27 mg/mL reducing sugars, 438.567 μg/mL TPC, 3.75 mg/mL FAN and 0.18% acidity which correlated with the predicted values ( Table 6). The experiments under the optimum conditions were in line with various model predictions (24,25) of the enzymatic saccharification process through RSM. Enzymatic saccharification through RSM in sugarcane top by microwave pretreatment was reported by Mauraya et al (26) and the optimal conditions obtained by RSM for sugarcane top were 50°C temperature and 72 h incubation time for maximum saccharification yield of reducing sugars (0.376 g/g glucose as a substrate).…”
Section: Model Fitting Of the Parameterssupporting
confidence: 74%
“…On the other hand the experimental values for the saccharification process were 3.27 mg/mL reducing sugars, 438.567 μg/mL TPC, 3.75 mg/mL FAN and 0.18% acidity which correlated with the predicted values ( Table 6). The experiments under the optimum conditions were in line with various model predictions (24,25) of the enzymatic saccharification process through RSM. Enzymatic saccharification through RSM in sugarcane top by microwave pretreatment was reported by Mauraya et al (26) and the optimal conditions obtained by RSM for sugarcane top were 50°C temperature and 72 h incubation time for maximum saccharification yield of reducing sugars (0.376 g/g glucose as a substrate).…”
Section: Model Fitting Of the Parameterssupporting
confidence: 74%
“…When the ratio was increased, the concentration of sugar was reduced. Phuengjayaem et al (2014) also studied the effect of substrate concentration of sorghum on its enzymatic saccharification using RSM and recorded a higher saccharification response (0.069 g/g of dry substrate) with a lower substrate concentration of 2.5% w/v, compared with 0.017 g/g obtained with a substrate concentration of 5.5% w/v. These results confirmed that increasing the substrate concentration of the enzymatic saccharification of biomass leads to slower saccharification because of an increased consistency and reduced surface contact between enzyme and substrate.…”
Section: Effect Of Substrate Concentrationmentioning
confidence: 99%
“…These authors achieved 83.27% saccharification efficiency at 50 °C and pH 5, which was higher than the 22.16% saccharification efficiency recorded at the temperature of 60 °C and pH 6. Phuengjayaem et al (2014) studied the effect of pH of the medium on the saccharification of sweet sorghum using RSM and found that at pH 5, 0.115 g/g of dried solid was obtained, compared with 0.00 g/g obtained at pH 7, even though the model predicted 0.026 g/g of dried solid.…”
Section: Effect Of Experimental Factors (Ph and Temperature)mentioning
confidence: 99%
See 2 more Smart Citations